From Green HRM to sustainability: A study of ground handling in java with employee performance as a key link - Ratih Puspitaningtyas Faeni; Dewi Puspaningtyas Faeni; Heni Pujiati; Yohannes Ferry Cahaya (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to examine the direct and indirect relationship between Green HRM variables, as well as provide theoretical and practical contributions in the development of environmentally friendly HR management strategies in the ground handling company. Research Methodology: Using a descriptive method with a purposive sampling technique. A total of 160 respondents from ground handling companies were used as samples. Primary data were collected through questionnaires (Google Form), and secondary data were obtained from various published sources. The analysis used included regression, correlation, percentage, and structural equation modeling. Results: Green recruitment, green training, and green performance appraisal significantly affect employee performance through the mediation of organizational sustainability. Environmentally oriented HR policies have been proven to improve organizational sustainability and employee performance. Conclusions: Green HRM practices have direct and indirect effects on employee performance and organizational sustainability. The integration of eco-friendly principles into HR strategies is essential for long-term productivity and sustainability. Limitations: This study was limited to companies in Java province, potential for questionnaire bias, the approach was only quantitative, and did not consider external factors such as organizational culture and leadership. Contributions: This research reinforces the importance of implementing GHRM to improve employee performance and organizational sustainability and encourages follow-up research with qualitative approaches and external factors.